Aberrant DNA Methylation Pattern may Enhance Susceptibility to Migraine: A Novel Perspective - Goel, Divya; Un Nisa, Kaiser; Reza, Mohammad I.; Rahman, Ziaur; Aamer, Shaikh (CNS & Neurological Disorders - Drug Targets, 2019)
In today’s world, migraine is one of the most frequent disorders with an estimated world prevalence of 14.7% characterized by attacks of a severe headache making people enfeebled and imposing a big socioeconomic burden. The pathophysiology of a migraine is not completely understood however there are pieces of evidence that epigenetics performs a primary role in the pathophysiology of migraine. Here, in this review, we highlight current evidence for an epigenetic link with migraine in particular DNA methylation of numerous genes involved in migraine pathogenesis. Outcomes of various studies have explained the function of DNA methylation of a several migraine related genes such as RAMP1, CALCA, NOS1, ESR1, MTHFR and NR4A3 in migraine pathogenesis. Mentioned data suggested there exist a strong association of DNA methylation of migraine-related genes in migraine. Although we now have a general understanding of the role of epigenetic modifications of a numerous migraine associated genes in migraine pathogenesis, there are many areas of active research are of key relevance to medicine. Future studies into the complexities of epigenetic modifications will bring a new understanding of the mechanisms of migraine processes and open novel approaches towards therapeutic intervention.
Keywords: Migraine